Association between urine uranium and asthma prevalence - Huang, Dongdong; Wang, Saibin (Frontiers in Public Health, 2024)
Background: Previous studies showed that urine Uranium (U) is associated with asthma prevalence in adults. However, the association between them among the general population is unclear. Therefore, this study aimed to explore this unclear association.The data of the participants were collected from the 2007-2016 National Health and Nutrition Examination Survey (NHANES) performed in the United States. Continuous variables with skewed distribution were analyzed using Ln-transformation. The association between urine U and asthma prevalence was analyzed by multiple regression analysis, and the linear association between them was evaluated by the smooth curve fitting. The subgroup analysis was performed using the hierarchical multivariate regression analysis.Results: A total of 13,581 participants were included in our analysis. The multivariate regression analysis showed that LnU was independently and positively correlated with asthma prevalence in the general population (OR=1.12; 95% CI:1.04,1.20; P=0.002). The subgroup analysis revealed that the College Graduate or above showed a stronger association between LnU and asthma prevalence (<9 th